The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.avb.2009.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Street gang theory and research: Where are we now and where do we go from here?

Abstract: Recent years have seen an upsurge of attention paid to street gangs as scholars and criminal justice officials strive to understand and counteract the effects of gang membership. Yet, despite a wealth of theoretical frameworks and empirical findings, even fundamental issues such as an agreed definition continue to elude us. We consider some of the most influential theoretical frameworks and associated empirical findings and find that as it stands, our knowledge on gangs is still limited and rather muddy. We su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(142 citation statements)
references
References 64 publications
2
139
1
Order By: Relevance
“…The new implication of our finding for theories of VYG is that we have demonstrated that the relationship between observed micro-place disorder and VYG is not just a matter of social controls, self-control and lifestyle risk but also a matter of subjective powerlessness. Subjective powerlessness fits in as a concept in Wood and Alleyne's (2010) unified framework of gang membership but it may also fit in Thornberry's interactional theory. The study of subjective powerlessness is important for practitioners and individuals that are high in subjective powerlessness are harder to motivate than individuals that are low in subjective powerlessness.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The new implication of our finding for theories of VYG is that we have demonstrated that the relationship between observed micro-place disorder and VYG is not just a matter of social controls, self-control and lifestyle risk but also a matter of subjective powerlessness. Subjective powerlessness fits in as a concept in Wood and Alleyne's (2010) unified framework of gang membership but it may also fit in Thornberry's interactional theory. The study of subjective powerlessness is important for practitioners and individuals that are high in subjective powerlessness are harder to motivate than individuals that are low in subjective powerlessness.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The bottom line is that subjective powerlessness / external locus of control is a concept that keeps popping up in criminological theories. It has recently been argued by Wood and Alleyne (2010) that the study of VYG needs to bring in more elements of psychology such as internal processes (cognitions, learned beliefs, …) that interact with the environment. By reintroducing the learned cognitive belief of subjective powerlessness we attempt to do so in both a theoretical and empirical way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organization gradually loses the ability to control the behavior of its members. There is no functional authority over potential white-collar criminals in the organization (Wood and Alleyne, 2010). As a consequence of social disorganization, organizational opportunity to commit white-collar crime increases (Hoffmann, 2002;Swart and Kinnie, 2003).…”
Section: Organizational Dynamicsmentioning
confidence: 99%
“…The individual will go on to commit crime if the person is exposed more to attitudes that favor law violation than attitudes that favor abiding by the law (Hoffmann, 2002;Wood and Alleyne, 2010).…”
Section: Organizational Dynamicsmentioning
confidence: 99%